Penerapan Program Lempuyang Pencak Silat Group (LPSG) Sebagai Upaya Peningkatan Potensi Desa Lempuyang Menjadi Desa Olahraga Mandiri - Setiadi, Khairul Mada; Puspitawati, Ratna Ayu; Nurdiansyah, Assa Saessar; Pradana, Anugrah Rizki; Ananda Ahnaf (Universitas Negeri Semarang, 2025)
Lempuyang Sports Village, which has undergone a transformation into a sports village since 2019, faces challenges in optimizing its sports potential, especially pencak silat. The Lempuyang Pencak Silat Group (LPSG) program implemented on August 20, 2023 aims to improve the capacity of coaches and referees, as well as introduce the latest regulatory standards. Evaluation of the training showed significant improvements in understanding and management of matches, with measurable results from a decrease in disqualifications and an increase in the quality of competition. LPSG Cup 1, which was implemented on August 26, 2023, succeeded in providing a fair and effective competition platform for local athletes, although the number of participants was still limited to the arts category. This program is expected to develop further, add competition categories, and attract more participants in the future, to strengthen Lempuyang Village's position as a center for pencak silat development in Demak Regency.